A Development in Direct Borohydride/Hydrogen Peroxide Fuel Cell Using Nanostructured Ni‐Pt/C Anode. Issue 3 (27th April 2017) - Abdolmaleki, M.; Hosseini, M. G.
Abstract: A direct borohydride fuel cell (DBFC) using H2 O2 as oxidizer has been developed. The NaBH4 /H2 O2 fuel cell is assembled by using Ni‐Pt/C composite as anode catalyst, Pt/C as cathode catalyst, and Nafion ® membrane as electrolyte. The compositions, morphology and particle sizes and of catalysts are evaluated by means of scanning electron microscopy (SEM), energy‐dispersive X‐ray spectroscopy (EDS), scanning electron microscopy and transmission electron microscopy (TEM), respectively. TEM images show that Ni‐Pt/C nanoparticles have an even size distribution with an average diameter of less than 20 nm. In this work, DBFC performance is studied under different operation conditions including operation temperature, borohydride concentration, and oxidant concentration. The experimental results show that the power density increased by increasing the temperature and increasing the concentration of oxidant. Experiments also show that electrochemical performance is not considerably affected by NaBH4 concentration. So that, it is found that 1.5M NaBH4 concentration is optimum for DBFC operation. A maximum power density of 140 mW cm −2 or 0.11 mW µg −1 Pttotal has been achieved at a cell voltage of 1.011 V at 55 °C. The cell is operated for about 72 h and its performance stability is recorded.